Back Cover: Conformational Spin Switching and Spin‐Selective Hydrogenation of a Magnetically Bistable Carbene (Angew. Chem. Int. Ed. 42/2019). Issue 42 (12th September 2019) - Trosien, Iris; Mendez‐Vega, Enrique; Thomanek, Tobias; Sander, Wolfram
Abstract : The spin state (singlet or triplet) of a magnetically bistable carbene is controlled by a remote methoxy group as a conformational switch. In their Communication on page 14855 ff., W. Sander et al. show how this conformational spin switching can be used to study the spin dependence of reactions and that it has potential applications in the design of novel switchable magnetic materials.